Acceptance and Refusal Rates for Stem Cell Transplantation and Donation among Saudi Females - Alrehaili, Amani; Alshihri, Sarah; Althobaiti, Rahaf; Alazizi, Nojoud; Gharib, Amal; Bakhuraysah, Maha; Alzahrani, Hind; Alhuthali, Hayaa (Jordan Medical Journal, 2023)
Background: The major obstacle to stem cell transplantation (SCT) therapy is finding a matching family donor. In Saudi Arabia, 60% of pediatrics and 30% of adult patients cannot find a matching donor in their family. Little evidence has been published worldwide to assess women’s acceptance of SCT, and so this research analyzed awareness of SCT and the acceptance and refusal rates for stem cell donation among Saudi females. Methods: A cross-sectional study was conducted with females living in Saudi Arabia. Voluntary questionnaires of 20 multiple-choice questions consisting of demographics, knowledge, and acceptance and refusal rates for SCT and donation were randomly distributed across social media platforms. Results: A total of 474 ‎participants completed the questionnaire. Participants showed low levels of basic knowledge regarding SCT: 20.9% gave the correct answer for stem cell sources, 27.6% were aware of SCT centers, and 36.9% were aware of the possible factors affecting the success of SCT. A low percentage (1.3%) of respondents were registered at the Saudi Stem Cell Donor Registry (SSCDR). The internet and social media, in particular, were the major sources of knowledge for half the participants. Interestingly, even though some participants expressed concerns, three-quarters stated their acceptance of SCT and donation, especially if there is a need. Conclusion: The females’ lack of knowledge about SCT and concerns about stem cell donation may contribute to the shortage of donor availability, suggesting a need to increase the level of awareness and motivation, particularly via health professionals.